The poetry of indifference - Gray, Erik Irving, 1972- (Amherst : University of Massachusetts Press, 2005)
"The Poetry of Indifference analyzes nineteenth-century works by Wordsworth, Keats, Byron, Tennyson, Robert Browning, and Edward FitzGerald, among others - works that do not merely declare themselves to be indifferent but formally enact the indifference they describe. Each poem consciously disregards some aspect of poetry that is usually considered to be crucial or definitive, even at the risk of seeming "indifferent" in the sense of "mediocre." Such gestures discourage critical attention, since the poetry of indifference refuses to make claims for itself." "This is particularly true of FitzGerald's Rubaiyat, one of the most popular poems of the nineteenth century, but one that recent critics have almost entirely ignored. In concentrating on this underexplored mode of poetry, Gray not only traces a major shift in recent literary history, from a Romantic poetics of sympathy to a Modernist poetics of alienation, but also considers how this literature can help us understand the sometimes embarrassing but unavoidable presence of indifference in our lives."--Jacket.
The Poetry of Indifference -- Indifference and Epistolarity in The Eve of St. Agnes -- Don Juan and the Poetics of Tourism -- "Strangely falls our Christmas-eve": Tennyson and Poetic Ambition -- Forgetting FitzGerald's Rubaiyat -- FitzGerald, Browning, and the Limits of Indifference.
Includes bibliographical references (pages 141-147) and index.
Keywords: English poetry -- 19th century -- History and criticism; Indifferentism (Ethics) in literature; Romanticism -- Great Britain; Histoire et critique; Romantisme -- Grande-Bretagne.; English poetry; Indifferentism (Ethics) in literature; Romanticism; Great Britain; Indifferenz; Romantik; Lyrik; English poetry -- 19th century -- History and criticism; Indifferentism (Ethics) in literature; Romanticism -- Great Britain; romantisme -- 19e s; Englisch; 1800-1899; Criticism, interpretation, etc